Examining the presence of the monday effect on the Indonesian Stock Exchange before and during the Covid-19 pandemic - Arya Suryanegara; Irene Rini Demi Pangestuti (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2024)
This study examines the presence of the Monday effect on the Indonesian Stock Exchange before and during the Covid-19 pandemic based on stock return, transaction volume, and trading patterns. This study uses trading day and trading hour as independent variables and daily return, daily total transaction volume, and return 30-minute intervals return within a day as a proxy for daily investor trading patterns as dependent variables. The data used in this study are from the Jakarta Composite Index from 1 July 2017 to 30 November 2022. The analytical methods used in this research is one-way ANOVA and two-way ANOVA. The results of this study demonstrate that day-of-week was not a significant factor in terms of daily return and daily total transaction volume before and during the pandemic. Moreover, there was no Monday effect in daily investor trading patterns before the pandemic. During the pandemic, the Monday effect in daily investor trading patterns was also not present. However, after the change in the trading hour period, the Monday effect was found in the daily investor trading pattern.